LabVIEW based monitoring and rehabilitation module for freezing of gait in Parkinson's disease. (2nd January 2019) - Mahajan, Abhishek; Swarnalatha, R.; Sherwani, Kashif; Kumar, Neelesh
Abstract: Freezing of gait (FOG) is an episodic motor symptom that occurs in almost half of the patients having Parkinson's Disease (PD). Levodopa and other dopaminergic drugs, although quite effective for tremors and bradykinesia (dyskinesia) are not so effective in case of postural instability and freezing of gait. This establishes a need for a non-pharmacological intervention. It has been well established in research that PD patients who experience FOG respond positively to sensory cueing. In this paper, a complete modular system has been developed that has both: (i) biofeedback in the form of vibrational cueing, synchronised with gait (hardware), as well as (ii) real-time monitoring, and graph generation for offline analysis (software). To realise this, a force sensor fitted shoe is constructed to analyse gait and provide vibrations in sync with phases of gait, for rehabilitation therapy. The assembly is monitored on LabVIEW, where (i) a 5-level force heat map and a 3D pressure map qualitatively shows the force experienced by force sensing resistors (FSR), (ii) an indicator for each vibrational motor shows its on/off state, and (iii) a live voltage vs. time graph (separate for each foot) is generated.